2022
DOI: 10.3389/fmed.2021.809395
|View full text |Cite
|
Sign up to set email alerts
|

Wired to Doubt: Why People Fear Vaccines and Climate Change and Mistrust Science

Abstract: We all want to be right in our thinking. Vaccine hesitancy and global warming denial share much in common: (1) both are threats to personal, community and global health, (2) action is contingent on co-operation and social policy, and (3) public support relies on trust in science. The irony is, however, as the science has become more convincing, public opinion has become more divided. A number of early polls showed that ~70% of people supported COVID-19 vaccine use and global warming, ~20% adopted a wait-and-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
(161 reference statements)
0
8
0
Order By: Relevance
“…In this study, the finding of high levels of endorsement of conspiracy beliefs about emerging virus infection was an anticipated outcome. In the current milieu of the continuous emergence of infectious diseases, the embrace of conspiratorial explanations escalates due to fear and uncertainty [ 82 ]. In our previous study among the general population residing in Jordan, 57% of the study participants believed that SARS-CoV-2 origin was related to biological warfare [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the finding of high levels of endorsement of conspiracy beliefs about emerging virus infection was an anticipated outcome. In the current milieu of the continuous emergence of infectious diseases, the embrace of conspiratorial explanations escalates due to fear and uncertainty [ 82 ]. In our previous study among the general population residing in Jordan, 57% of the study participants believed that SARS-CoV-2 origin was related to biological warfare [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in the United States, skepticism was strongly associated with a reduction in prevention behaviors [43]. As it is a highly transmissible infection, individual freedom to adopt prevention behaviors has been widely discussed since the individual option can harm others or society in general [44].…”
Section: Resultsmentioning
confidence: 99%
“…As the public is increasingly attuned to the term “pandemic” and have increasing beliefs that climate change is happening ( Leiserowitz et al, 2021 ), it is important for public health professionals to cease this opportunity to communicate how climate change and globalization can affect emerging infectious diseases ( Whitmee et al, 2015 ; Intergovernmental Panel on Climate Change [IPCC], 2021 ). Furthermore, by understanding this connection, the public potentially could be more willing to accept political or societal changes for climate change or pandemic mitigation ( Dobson, 2022 ; Latkin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 (COVID-19) virus is a disease of zoonotic origin that resulted in a global health crisis. People's doubts or beliefs of climate change are related to (dis-)concern for COVID-19 ( Dobson, 2022 ; Latkin et al, 2022 ; Kulcar et al, 2022 ). For example, in a recent study about views of climate change and COVID-19, researchers found higher climate change concerns were associated with a 2-times higher perceived risk for COVID-19 ( Latkin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%